Das Zylinder-Fragment Nr. 1+6, Gudeas Zylinder X und Ninĝirsus Heldentaten im Gebirge: Textedition und -rekonstruktion - Gabriel, Gösta (Altorientalische Forschungen, 2022)
This paper investigates the Lagash II cylinder fragment Nr. 1+6, whose physical join can be confirmed. A new edition of the joined fragment provides a more comprehensive understanding. Furthermore, the question is raised of whether this fragment might have belonged to the hypothesized Gudea Cylinder X. If this question could be answered in the affirmative, the fragment would point to the existence of a three-partite praise song (za₃-mim) addressing Ninĝirsu. However, also without such a connection the fragment allows for a more comprehensive understanding of Ninĝirsu’s adventures in the mountain lands.